An oxidation responsive nano-radiosensitizer increases radiotherapy efficacy by remolding tumor vasculature. (17th August 2021) - Wang, Xiaohui; Niu, Xiaoyan; Sha, Weizhou; Feng, Xiaoyue; Yu, Licheng; Zhang, Zhenjie; Wang, Wei; Yuan, Zhi
Abstract : An amazing nanoplatform (Au@SA-QBA) was utilized to specifically normalize tumor vessels and significantly improve the radiotherapy effect. Abstract : As an excellent candidate material for nano-sensitizers, gold nanostructures have shown great potential in radiotherapy. Nevertheless, severe hypoxia and low accumulation of nanomedicine caused by poor perfusion at the tumor site have significantly reduced radiotherapy efficacy. Vascular normalization has gained attention owing to its ability to relieve hypoxia and increase perfusion. The synergistic therapy of tumor vascular normalization and radiotherapy has become a new option to increase anti-cancer efficacy. However, the commonly used strategy of suppressing a single growth factor to induce vascular normalization is limited by tumor compensatory effects. In this work, we developed a strategy to inhibit oxidative stress in tumors by generating chelating agents in response to hydrogen peroxide, thereby inhibiting multi-angiogenic factors simultaneously to normalize blood vessels. Concretely, sodium alginate (SA) reacted with 8-quinoline boric acid (QBA) to form SA-QBA. Then gold nanoparticles (Au NPs) were modified with SA-QBA to obtain Au@SA-QBA. The system was simple in structure and could generate 8HQ in response to H2 O2 in vitro to inhibit oxidative stress and reduce the expression of VEGF, bFGF, and Ang-2. In vivo, the perfusion unit (PU) increased by 78% after Au@SA-QBA treatment, and the coverage of pericytes increased by 32%, which in turn induced vascular normalization. In addition, blood routine and blood biochemical tests confirmed its good biocompatibility and 8HQ was not detected in the supernatant after homogenization of major organs. More importantly, after the synergistic treatment of vascular normalization and radiotherapy (4 Gy), the tumor growth inhibition rate was increased by 38.6% compared to the Au@SA-treated group with negligible side effects to normal tissues.